Obstructive Jaundice with skin involvement - An unusual presentation of Myeloid Sarcoma - Pukhraj S Jeji; Swarup K Patnaik; Manas K Behera; Jimmy Narayan; Manoj K Sahu; Debakanta Mishra; Ayaskanta Singh; Girish K Pati (Wolters Kluwer Medknow Publications, 2023)
Biliary obstruction secondary to malignancy is a common clinical problem. Rarely, biliary obstruction is due to leukemia, and obstructive jaundice in these patients usually presents late in the course of the disease. We present a rare case of a patient who presented with fever, jaundice, and pruritus with multiple nodular swellings in the left shoulder, left thigh, and lower back. Magnetic resonance cholangiopancreatography (MRCP) revealed periampullary mass lesion causing dilated common bile duct (CBD) and intrahepatic bile ducts; hence, endoscopic retrograde cholangiography with plastic stenting was done. Biopsy from the shoulder lesion revealed a mesenchymal tumor, and immunohistochemistry (IHC) confirmed the lesion as myeloid sarcoma. Myeloid sarcoma is an extramedullary tumor, a subtype of acute myeloid leukemia, and presentation as biliary lesions with multiple anatomical sites is very rare. The patient was started on chemotherapy after the normalization of bilirubin. The patient showed improvement of skin lesions and normalization of liver function test (LFT) after 3 weeks of chemotherapy.